From Distance Education to Open and Distance Learning: A Holistic Evaluation of History, Definitions, and Theories - Bozkurt, Aras; Bozkurt, Aras (http://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-5225-8431-5.ch016, 2001)
As pragmatist, interdisciplinary fields, distance education (DE) and open and distance learning (ODL) transform and adapt themselves according to changing paradigms. In this regard, the purpose of this study is to examine DE and ODL from different perspectives to discern their future directions. The study concludes that DE and ODL are constantly developing interdisciplinary fields where technology has become a significant catalyst and these fields become part of the mainstream education. However, mainstreaming should be evaluated with caution, and there is a need to revisit core values and fundamentals where critical pedagogy would have a pivotal role. Besides, there is no single theory that best explains these interdisciplinary fields, and therefore, there is a need to benefit from different theoretical approaches. Finally, as a result of constant changes, we should keep the definition of both DE and ODL up-to-date to better explain the needs of the global teaching and learning ecosystem.